Toxicological safety evaluation of pasteurized Akkermansia muciniphila. Issue 2 (28th July 2020) - Druart, Céline; Plovier, Hubert; Van Hul, Matthias; Brient, Alizée; Phipps, Kirt R.; de Vos, Willem M.; Cani, Patrice D.
Abstract: Gut microorganisms are vital for many aspects of human health, and the commensal bacterium Akkermansia muciniphila has repeatedly been identified as a key component of intestinal microbiota. Reductions in A. muciniphila abundance are associated with increased prevalence of metabolic disorders such as obesity and type 2 diabetes. It was recently discovered that administration of A. muciniphila has beneficial effects and that these are not diminished, but rather enhanced after pasteurization. Pasteurized A. muciniphila is proposed for use as a food ingredient, and was therefore subjected to a nonclinical safety assessment, comprising genotoxicity assays (bacterial reverse mutation and in vitro mammalian cell micronucleus tests) and a 90‐day toxicity study. For the latter, Han Wistar rats were administered with the vehicle or pasteurized A. muciniphila at doses of 75, 375 or 1500 mg/kg body weight/day (equivalent to 4.8 × 10 9, 2.4 × 10 10, or 9.6 × 10 10 A. muciniphila cells/kg body weight/day) by oral gavage for 90 consecutive days. The study assessed potential effects on clinical observations (including detailed arena observations and a modified Irwin test), body weight, food and water consumption, clinical pathology, organ weights, and macroscopic and microscopic pathology. The results of both in vitro genotoxicity studies were negative. No test item‐related adverse effects were observed in the 90‐day study; therefore, 1500 mg/kg body weight/day (the highest dose tested, equivalent to 9.6 × 10 10 A. muciniphila cells/kg body weight/day) was established as the no‐observed‐adverse‐effect‐level. These results support that pasteurized A. muciniphila is safe for use as a food ingredient. Abstract : Pasteurized A. muciniphila is proposed for use as a food ingredient and was therefore subjected to in vitro genotoxicity tests and a 90‐day oral (gavage) toxicity study in rats. There was no evidence of genotoxicity, and the highest dose tested in the 90‐day study (1500 mg/kg body weight/day, equivalent to 9.6 × 10 10 A. muciniphila cells/kg body weight/day) was established as the no‐observed‐adverse‐effect‐level. These results support the safety of pasteurized A. muciniphila for use as a food ingredient.